Digital transformation of a big city as an object of sociological analysis - Lebedeva, Еlena V. (Journal of the Belarusian State University. Sociology, 2022)
The article presents a sociological analysis of the digital transformation phenomenon (the case of Minsk). The chronology of the stages of the formation of scientific discourse about this phenomenon (automation, digitisation, digitalisation and digital transformation) is described. Specific indicators of the sociological dimension of the digital transformation of the city based on empirical data are proposed (the ratio of digital and traditional methods of solving applied problems, the exit of digital technologies beyond their utilitarian use, motivation for the development of new technologies). Using the obtained indicators, a typology of digital types of citizens is constructed.
Keywords: urban environment; smart city; digital transformation; empirical indicators; digital types of citizens